A CONSTRUÇÃO DE UMA ASSESSORIA-ESCOLA NA FORMAÇÃO DO PSICÓLOGO - Veronese, Luciane G.; Heidemann, Nilson; Sand, Adriana P. V. D.; Hedlund, Ana C. B.; Oliveira, Angela M. K.; Avila, Cassiana A.; Silveira, Edson S. d.; Woff, Marcella; Marin, Mariana B.; Aimi, Martina S.; et al. (Salão do Conhecimento, 2013)
Resumo